2002
DOI: 10.1046/j.1432-1033.2002.03042.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH homeostasis in the filamentous fungus Aspergillus niger

Abstract: Intracellular pH homeostasis in the filamentous fungus Aspergillus niger was measured in real time by 31 P NMR during perfusion in the NMR tube of fungal biomass immobilized in Ca 2+ -alginate beads. The fungus maintained constant cytoplasmic pH (pH cyt ) and vacuolar pH (pH vac ) values of 7.6 and 6.2, respectively, when the extracellular pH (pH ex ) was varied between 1.5 and 7.0 in the presence of citrate. Intracellular metabolism did not collapse until a DpH over the cytoplasmic membrane of 6.6-6.7 was rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 47 publications
4
51
0
Order By: Relevance
“…Consequently, proton fluxes occur across cellular membranes to maintain intracellular pH homeostasis (Hesse et al 2002). Upon transfer of growing A. oryzae biomass to 2% WLM, the intracellular pH decreases due to metabolic activity and, as a consequence of proton fluxes across the extra cellular membrane, the growth medium started to acidify.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, proton fluxes occur across cellular membranes to maintain intracellular pH homeostasis (Hesse et al 2002). Upon transfer of growing A. oryzae biomass to 2% WLM, the intracellular pH decreases due to metabolic activity and, as a consequence of proton fluxes across the extra cellular membrane, the growth medium started to acidify.…”
Section: Discussionmentioning
confidence: 99%
“…The pKa of the Venus chromophore is reported to be 6.0 [19]. At pH of 7.6, which is a reasonable estimate for the pH in fungal cells [32], there would be 2.5% of protonated acceptor.…”
Section: Accepted M Manuscriptmentioning
confidence: 93%
“…The acidophilic nature of A. niger is demonstrated by the finding that even under the extremely low ambient pH conditions of citric acid fermentation, the cytosolic and vacuolar (mitochondrial) compartments retain pH values of 7.5 and 6.1, respectively (Hesse et al, 2000(Hesse et al, , 2002. Additional investigations demonstrated that intracellular pH declines as dissolved oxygen concentration falls (Legiša and Grdadolnik, 2002).…”
Section: Citric Acidmentioning
confidence: 99%